Representation of Moral Values in the Film God Allows Me to Sin: Semiotic Studies and Its Implications in Indonesian Language Learning - Lilik Rita Sari (Universitas Muria Kudus, 2025)
This study aims to analyze the representation of moral values in the film God Allows Me to Sin using a descriptive qualitative approach with a semiotic perspective of Roland Barthes. The focus of the analysis is directed at visual and verbal symbols, codes, and signs that build moral meaning through characters, storylines, and other cinematic elements. Data were obtained through literature studies, direct observation of films, and documentation, and were analyzed based on the denotative and connotative meanings of the signs in the film. The results of the study show that the film represents moral values such as repentance and repentance, compassion and sacrifice, and justice and consequences through lighting, water symbols, body language, dialogue, and symbolic objects such as mirrors. These findings have significant implications for Indonesian language learning, especially in strengthening students' understanding of multimodal texts and developing character values through audiovisual media. This study suggests the integration of film semiotic studies in learning to improve students' visual literacy, critical thinking, and moral awareness.